Binary additive effect of benzoic acid in ipso-Friedel-Crafts-type dearomatization of phenols using a chiral silver phosphate. Issue 20 (17th May 2018) - Nakayama, Hiroki; Harada, Shingo; Kanda, Ayaka; Kwok, Irene Mei-Yi; Nemoto, Tetsuhiro
Abstract: We previously developed a chemoselective asymmetric phenol dearomatization using a silver catalyst and benzoic acid as an additive to enhance the reaction efficiency. The mechanistic role of the additive, however, remained unclear. Herein we describe detailed studies to elucidate the additive effect, which revealed that benzoic acid plays two supporting roles in the silver-catalyzed reaction. First, it promotes protonation of a silver enolate intermediate to improve the chemical yield of a spirolactam. Second, it dissociates a homochiral dimer of silver phosphate to generate a monomeric species. Graphical abstract: